merA gene expression in aquatic environments measured by mRNA production and Hg(II) volatilization. - Nazaret, S (1994)
The relationship of merA gene expression (specifying the enzyme mercuric reductase) to mercury volatilization in aquatic microbial communities was investigated with samples collected at a mercury-contaminated freshwater pond, Reality Lake, in Oak Ridge, Tenn. Levels of merA mRNA transcripts and the rate of inorganic mercury [Hg(II)] volatilization were related to the concentration of mercury in the water and to heterotrophic activity in field samples and laboratory incubations of pond water in which microbial heterotrophic activity and Hg(II) concentration were manipulated. Levels of merA-specific mRNA and Hg(II) volatilization were influenced more by microbial metabolic activity than by the concentration of mercury. merA-specific transcripts were detected in some samples which did not reduce Hg(II), suggesting that rates of mercury volatilization in environmental samples may not always be proportional to merA expression.